2022-RA-1071-ESGO Primary treatment and prognostic factors of neuroendocrine carcinoma of the uterine cervix. (20th October 2022) - Lee, Seoyoon; Kim, Se Ik; Lim, Hyun ji; Kim, Junhwan; Lee, Maria; Kim, Jae Won
Abstract : Introduction/Background: Neuroendocrine carcinoma of the cervix (NECC) is a rare, aggressive histologic type of cervical cancer. Currently, there is no standardized therapy for NECC. This study aims to investigate prognostic factors of NECC and compare survival outcomes according to the treatment methods. Methodology: NECC patients who received primary treatment at our institution between 2000 and 2020 were retrospectively identified. We collected patients' clinicopathologic and survival data, including age at diagnosis, histologic subtype, stage, immunohistochemical staining results, and detailed treatment methods. Multivariate analyses were conducted to identify prognostic factors for progression-free survival (PFS) and overall survival (OS). Results: In total of 47 NECC patients included, mean age at diagnosis was 46.9 years. The most common chief complaint was vaginal bleeding (61.7%). In relation to histologic subtypes, 23 (48.9%) and 7 (14.9%) were diagnosed with small cell and large cell NECCs, while the other 17 (36.2%) was combined with other carcinomas. Patients with early-stage (IB1) showed longest median PFS of 15.6 months, whereas shortest was with distant metastasis (IVB) of 7.0 months, with 94.7%, 15.6% 18-month OS rates, respectively. In multivariate analysis adjusting clinicopathologic variables, distant metastasis (adjusted HR, 7.941; 95% CI, 2.799–22.530; P<0.001) and small cell NECC (adjusted HR, 0.297; 95% CI, 0.133–0.663; P=0.003) were identified as poor and favorable prognostic factors for PFS. Distant site metastasis was also associated with worse OS (adjusted HR, 7.528; 95% CI, 1.666–34.007; P=0.009). In a subgroup of stage IVB NECC, no differences in PFS and OS were observed between the chemotherapy-only and combined therapy with two and more treatment modalities (P=0.0214 and P=0.357, respectively). Conclusion: Higher disease recurrence and mortality rates were observed in patients with NECC. Initial FIGO stage and histologic subtypes were significant prognostic factors for survival. For patients with stage IVB disease, chemotherapy only might be preferable rather than combined therapy.